Exercise-Induced Left Ventricular Remodeling Among Competitive Athletes: A Phasic Phenomenon. (December 2015) - Weiner, Rory B.; DeLuca, James R.; Wang, Francis; Lin, Jeffrey; Wasfy, Meagan M.; Berkstresser, Brant; Stöhr, Eric; Shave, Rob; Lewis, Gregory D.; Hutter, Adolph M.; Picard, Michael H.; Baggish, Aaron L.
Abstract : Background—: Contemporary understanding of exercise-induced cardiac remodeling is based on cross-sectional data and relatively short duration longitudinal studies. Temporal progression of exercise-induced cardiac remodeling remains incompletely understood. Methods and Results—: A longitudinal repeated-measures study design using 2-dimensional and speckle-tracking echocardiography was used to examine acute augmentation phase (AAP; 90 days) and more extended chronic maintenance phase (39 months) left ventricular (LV) structural and functional adaptations to endurance exercise training among competitive male rowers (n=12; age 18.6±0.5 years). LV mass was within normal limits at baseline (93±9 g/m 2 ), increased after AAP (105±7 g/m 2 ; P =0.001), and further increased after chronic maintenance phase (113±10 g/m 2 ; P <0.001 for comparison to post-AAP). AAP LV hypertrophy was driven by LV dilation (ΔLV end-diastolic volume, 9±3 mL/m 2 ; P =0.004) with stable LV wall thickness (ΔLV wall thickness, 0.3±0.1 mm; P =0.63). In contrast, chronic maintenance phase LV hypertrophy was attributable to LV wall thickening (Δ LV wall thickness, 1.1±0.4 mm; P =0.004) with stable LV chamber volumes (ΔLV end-diastolic volume, 1±1 mL/m 2 ; P =0.48). Early diastolic peak tissue velocity increased during AAP (−11.7±1.9 versus −13.6±1.3 cm/s; P <0.001) and remained similarly increased after chronic maintenance phase. Conclusions—: In a small sample of competitive endurance athletes, exercise-induced cardiac remodeling follows a phasic response with increases in LV chamber size, early diastolic function, and systolic twist in an acute augmentation phase of exercise training. This is followed by a chronic phase of adaptation characterized by increasing wall thickness and regression in LV twist. Training duration is a determinant of exercise-induced cardiac remodeling and has implications for the assessment of myocardial structure and function in athletes.